MODEL PROJECT CITIZENT DALAM MENINGKATKAN KECAKAPAN PENDIDIKAN KEWARGANEGARAAN PADA PENGEMBANGAN NILAI NILAI KARAKTER BUDAYA BANGSA - Sulaiman., Sulaiman; Nurmasyitah., Nurmasyitah (Jurnal Pesona Dasar, 2020)
Character development which is an effort to realize the mandate of the Pancasila and the Preamble to the 1945 Constitution is motivated by the reality of the national problems that are developing at this time, such as: disorientation and not living the values of Pancasila; the limitations of integrated policy tools in realizing the values of Pancasila; shifting ethical values in the life of the nation and state; waning awareness of national cultural values; the threat of national disintegration; and the weakening of the nation's independence (National Policy Master Book for the Development of the Nation's Cultural Character 2010-2025). To support the realization of the ideals of character development as mandated in the Pancasila and the Preamble to the 1945 Constitution and to overcome the current national problems, the Government has made character development as one of the national development priority programs. That spirit is implicitly emphasized in the National Long-Term Development Plan (RPJPN) for 2005-2015, where character education is placed as a foundation for realizing the vision of national development, namely "realizing a society of noble, moral, ethical, cultured, and civilized based on the Pancasila philosophy. " One model that can develop national cultural character values through citizenship education is the Project citizen model, which is a portfolio-based learning model. Through this model students are not only invited to understand scientific concepts and principles, but also develop their ability to work cooperatively through empirical practice learning activities. thus learning will be increasingly challenging, activating and more meaningfulÂ